1998
DOI: 10.1148/radiology.206.1.9423666
|View full text |Cite
|
Sign up to set email alerts
|

Segment 4 (the quadrate lobe): a barometer of cirrhotic liver disease at US.

Abstract: A decreased diameter of segment 4 may be a helpful adjunct sign of cirrhosis in the US investigation of chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Among imaging landmarks related to the segmental atrophy-hypertrophy complex and the secondary findings of portal hypertension [1][2][3][4][5], the combination of an expanded gallbladder fossa and the presence of a posteromedial notch on the right lobe of the liver has been suggested as a highly sensitive and specific sign with which to differentiate cirrhotic from normal liver [6,7]. Particularly for chronic viral hepatitis, the early recognition of cirrhotic change is essential for patients' management of the cirrhosis itself and for monitoring the development of hepatocellular carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among imaging landmarks related to the segmental atrophy-hypertrophy complex and the secondary findings of portal hypertension [1][2][3][4][5], the combination of an expanded gallbladder fossa and the presence of a posteromedial notch on the right lobe of the liver has been suggested as a highly sensitive and specific sign with which to differentiate cirrhotic from normal liver [6,7]. Particularly for chronic viral hepatitis, the early recognition of cirrhotic change is essential for patients' management of the cirrhosis itself and for monitoring the development of hepatocellular carcinoma.…”
mentioning
confidence: 99%
“…Particularly for chronic viral hepatitis, the early recognition of cirrhotic change is essential for patients' management of the cirrhosis itself and for monitoring the development of hepatocellular carcinoma. However, many of the previous reports mentioned only general morphological changes of the liver, irrespective of the histological grade or the cause of cirrhosis [1][2][3][4][5][6][7]. Recently, Aguirre et al [8] reported that double contrast-enhanced MRI (DC-MRI), including dynamic imaging using gadolinium contrast agent and subsequent delayed imaging following injection of superparamagnetic iron oxide (SPIO) particles, was similar to histological grading in scoring the hepatic fibrosis associated with cirrhotic changes.…”
mentioning
confidence: 99%
“…This is due to the unique anatomical direction of the portal venous flow observed with using color Doppler ultrasonography (22). The flow in the portal vein branches of the LS and the CL is uniformly hepatopetal, whereas the MS often receives circular or hepatofugal flow from the right side of the umbilical segment with less blood than the other segments (23). Even during early fibrosis, which cannot be grossly depicted on DC-MRI, the overall portal venous perfusion is usually reduced in the entire liver, and the flow to the MS would be more deteriorated and minimized earlier than the flow in the other segments, resulting in segmental atrophy (23).…”
Section: Discussionmentioning
confidence: 99%
“…The flow in the portal vein branches of the LS and the CL is uniformly hepatopetal, whereas the MS often receives circular or hepatofugal flow from the right side of the umbilical segment with less blood than the other segments (23). Even during early fibrosis, which cannot be grossly depicted on DC-MRI, the overall portal venous perfusion is usually reduced in the entire liver, and the flow to the MS would be more deteriorated and minimized earlier than the flow in the other segments, resulting in segmental atrophy (23). For the high prevalence of expanded gallbladder fossa signs regardless of the intersegmental difference between the MS and the LS in the present study, the expanded gallbladder fossa sign may develop before the gross appearance of reticular fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…By combining sonographic symptoms of B-mode imaging in a common system several researchers have gained increment of specificity of the method (Nishiura et al, 2005). Liver cirrhosis is characterized by changes in liver size and its proportion: atrophy of the right lobe and the medial segment of the left lobe as well as hypertrophy of lobus caudatus and the lateral segment of the left lobe (Giorgio et al, 1986;Lafortune et al, 1998). In total, the diagnostic accuracy of US in detection of liver cirrhosis is high enough, while its applicability in precirrhotic stages of the disease is limited.…”
Section: Patientsmentioning
confidence: 99%